Implementing and optimizing the operation of membrane bioreactors for petroleum wastewater treatment - Inglezakis, V.; Fatone, F.; Malamis, S.; Loizidou, M.; Seidakhmetov, T.; Omirkhan, A. (Nazarbayev University, 2013)
The main objective of the project is to study & optimize the operation of a membrane bioreactor (MBR) coupled with suitable pre-treatment for the treatment of petroleum wastewater. The optimization will focus on the configurations to achieve the desired treated effluent quality.
Keywords: first research week; oil and gas industry; membrane bioreactor; treatment of petroleum wastewater